Arabic Grammatical and Morphological Issues: Adding Letters And Changing Meanings/ القضايا النحوية والصرفية في اللغة العربية: إضافة الحروف وتغيير المعاني - Gumilar, Rizki (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The issue of increasing the structure indicates an increase in meaning, which has been an issue since the era of Ibn Jinni (392 AH). The researcher saw that it appeared several times in Ibn Taymiyyah’s works to support his opinion when he derived rulings on Arabic grammatical and morphological issues. This research reveals the application of this issue from the sayings of Ibn Taymiyyah and compares it with the opinions of previous grammarians. The method used in this research is the descriptive and analytical method, and it was implemented by collecting applications for this issue from the books of Ibn Taymiyyah, extracting them, and comparing them with what was mentioned in the books of grammarians. This research reveals the phenomena of increasing the structure, indicating an increase in meaning, according to Ibn Taymiyyah, in all three elements of the language: sound, morphology, and structure. At the sound level, three topics are addressed: grammatical, singular, dual, and plural signs, as well as linguistic differences between words. At the level of morphology, there are two topics: increasing the hamza and extending the sound. At the level of structure, three issues are discussed: increasing restrictions, repeating pronunciation, and increasing prepositions. Ibn Taymiyyah saw a strong and constant relationship between the structure and the meaning. The strength of the structure is due to the strength of the meaning, and its weakness is due to its weakness. This issue exists in all the various languages in the world. The researcher also cited the sayings of grammarians commenting on Ibn Taymiyyah’s opinion. Perhaps this research contributes to thinking about the Arabic language and how it is taught.